Cross-sectional association between objective cognitive performance and perceived age-related gains and losses in cognition - Sabatini, Serena; Ukoumunne, Obioha C.; Ballard, Clive; Collins, Rachel; Anstey, Kaarin J.; Diehl, Manfred; Brothers, Allyson; Wahl, Hans-Werner; Corbett, Anne; Hampshire, Adam; Brooker, Helen; Clare, Linda (International psychogeriatrics, 2021)
Objectives: - Evidence linking subjective concerns about cognition with poorer objective cognitive performance is limited by reliance on unidimensional measures of self-perceptions of aging (SPA). We used the awareness of age-related change (AARC) construct to assess self-perception of both positive and negative age-related changes (AARC gains and losses). We tested whether AARC has greater utility in linking self-perceptions to objective cognition compared to well-established measures of self-perceptions of cognition and aging. We examined the associations of AARC with objective cognition, several psychological variables, and engagement in cognitive training. - Design: - Cross-sectional observational study. - Participants: - The sample comprised 6056 cognitively healthy participants (mean [SD] age = 66.0 [7.0] years); divided into subgroups representing middle, early old, and advanced old age. - Measurements: - We used an online cognitive battery and measures of global AARC, AARC specific to the cognitive domain, subjective cognitive change, attitudes toward own aging (ATOA), subjective age (SA), depression, anxiety, self-rated health (SRH). - Results: - Scores on the AARC measures showed stronger associations with objective cognition compared to other measures of self-perceptions of cognition and aging. Higher AARC gains were associated with poorer cognition in middle and early old age. Higher AARC losses and poorer cognition were associated across all subgroups. Higher AARC losses were associated with greater depression and anxiety, more negative SPA, poorer SRH, but not with engagement in cognitive training. - Conclusions: - Assessing both positive and negative self-perceptions of cognition and aging is important when linking self-perceptions to cognitive functioning. Objective cognition is one of the many variables - alongside psychological variables - related to perceived cognitive losses.